Pengaruh NPL Dan LDR Terhadap ROA Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2022 - Yeni, Darlisa Putri; Purba, Purnama Yanti; Tambunan, Cklaudya Julianti Morina; Marbun, Hara Artha Ulina; Putri, Tantri Octora Dwi Syah (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2024)
This research aims to determine and analyze the influence of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) in banks listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. Financial reports are presented to fulfill several different information needs, one of which is information about profits. This information is very important because profit explains how the company performs during a period. The type of data used is secondary data obtained from financial reports downloaded via the official website of the Indonesia Stock Exchange (BEI). The sampling technique was purposive sampling, totaling 108 samples. The data analysis method used is Multiple Linear Regression. The results of the research show that partially Non Performing Loans (NPL) have a positive and significant effect on Return On Assets (ROA) and Loan to Deposit Ratio (LDR) has no effect on Return On Assets (ROA) in banks listed on the Indonesian Stock Exchange (BEI ) period 2020-2022. Simultaneously Non Performing Loans (NPL) and Loan To Deposit Ratio (LDR) have a positive and significant effect.